Early intervention in asymptomatic external iliac artery stenosis: How important is it? - Catelya, Laras Gaby; Kurnianingsih, Novi; Rohman, Mohammad Saifur (Heart Science Journal, 2026)
Background: Aortoiliac occlusive disease (AIOD) represents a clinical manifestation of systemic atherosclerosis, which may progress into Chronic Limb-Threatening Ischemia (CLTI) and contribute to an increased risk of cardiovascular death. Case illustration: A 62-year-old male presented to the clinic for staged percutaneous coronary intervention without complaint of intermittent claudication. Higher pulsation was palpable in the right femoral artery, with an Ankle-Brachial Index (ABI) of 0.8. The PCI procedure was then carried out using left femoral artery access. Following the procedure, a Duplex ultrasound (DUS) evaluation of the lower extremity was done, with no remarkable stenosis found. CT angiography revealed severe stenosis of the right external iliac artery with a TASC II C lesion. Digital subtraction angiography (DSA) was then performed using right brachial artery access, revealing an 80% stenosis of the right medial external iliac artery. Based on the measurement, angioplasty was done, followed by stent implantation of the right external iliac artery using Abbott Vascular Omnilink Elite 7x39 mm 135 cm with a pressure of 11 atm for 30 seconds. Following the procedure, an improvement in distal arterial flow of the right lower extremity was observed, as indicated by ABI and DUS evaluation. The rest of the hospital stay was uneventful. The patient was discharged the next day after the procedure, without any residual symptoms. Conclusion: Patients with asymptomatic PAD are at very high cardiovascular risk. Early intervention of PAD may prevent its progression into CLTI. Endovascular revascularisation of the aortoiliac lesions in suitable patients grants satisfactory results with fewer drawbacks.